HCC incidence after hepatitis C cure among patients with advanced fibrosis or cirrhosis: A meta‐analysis. Issue 1 (7th February 2022) - Lockart, Ian; Yeo, Malcolm G. H.; Hajarizadeh, Behzad; Dore, Gregory J.; Danta, Mark
Abstract: Background and Aims: HCV cure reduces but does not eliminate the risk of HCC. HCC surveillance is recommended in populations where the incidence exceeds 1.5% per year. In cirrhosis, HCC surveillance should continue after HCV cure, although it is uncertain if this should be indefinite. For patients with advanced fibrosis (F3), guidelines are inconsistent in their recommendations. We evaluated the incidence of HCC after HCV cure among patients with F3 fibrosis or cirrhosis. Approach and Results: This systematic review and meta‐analysis identified 44 studies (107, 548 person‐years of follow‐up) assessing the incidence of HCC after HCV cure among patients with F3 fibrosis or cirrhosis. The incidence of HCC was 2.1 per 100 person‐years (95% CI, 1.9–2.4) among patients with cirrhosis and 0.5 per 100 person‐years (95% CI, 0.3–0.7) among patients with F3 fibrosis. In a meta‐regression analysis among patients with cirrhosis, older age (adjusted rate ratio [aRR] per 10‐year increase in mean/median age, 1.32; 95% CI, 1.00–1.73) and prior decompensation (aRR per 10% increase in the proportion of patients with prior decompensation, 1.06; 95% CI, 1.01–1.12) were associated with an increased incidence of HCC. Longer follow‐up after HCV cure was associated with a decreased incidence of HCC (aRR per year increase in mean/median follow‐up, 0.87; 95% CI, 0.79–0.96). Conclusions: Among patients with cirrhosis, the incidence of HCC decreases over time after HCV cure and is lowest in patients with younger age and compensated cirrhosis. The substantially lower incidence in F3 fibrosis is below the recommended threshold for cost‐effective screening. The results should encourage the development of validated predictive models that better identify at‐risk individuals, especially among patients with F3 fibrosis. Abstract : image